PROBLEMATIKA YANG MUNCUL KARENA PENERBITAN SERTIPIKAT HAK ATAS TANAH ELEKTRONIK - Rio Prasetio (Fakultas Hukum Universitas Narotama, 2022)
Changes in the era of the industrial revolution 4.0. In this case, all activities that support life are made easier by the presence of technology to make it more practical and efficient. In the field of Land Law, in order to realize the improvement of land services, starting to implement electronic-based land services, to the documents produced in the form of electronic documents. Land reform is very much needed to improve services to the community, aiming to re-register land ownership, use and utilization of agrarian resources, especially land in order to achieve accuracy, certainty, and legal protection quickly, even to avoid the existence of land mafias. The Ministry of Agrarian Affairs and Spatial Planning issues Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 1 of 2021 concerning Electronic Certificates. The results of this study indicate that: (i) the phrase